Self-control stability and change for incarcerated juvenile offenders. (May 2018) - Hay, Carter; Widdowson, Alex; Young, Brae Campion
Abstract: Purpose: Few studies have examined self-control stability with samples of serious offenders. This study examined incarcerated juvenile offenders to determine (1) if changes in self-control occur during confinement and (2) whether self-control changes affect functioning inside the facility and reoffending after release. Methods: The analysis used data from a sample of male and female juvenile offenders in Florida who were released from a residential program in 2010–11. Self-control and functioning inside the facility were measured with risk assessment data collected at the beginning and end of the residential confinement. Reoffending was assessed for the 12 months after release. Results: Absolute and relative changes in self-control were common, and the absolute changes overwhelmingly involved improvement. This led to improved functioning inside the facility and decreased odds of adjudication for a new offense. Follow-up analyses revealed a key difference between males and females—for reoffending in particular, effects of self-control change were observed only among females. Conclusions: Juvenile confinement in settings with evidence-based rehabilitation programming can produce self-control improvement. These improvements, in turn, are associated with contemporaneous improvements in behavior during confinement. These shifts also may lower recidivism after release, but this pattern appears less likely among males. Highlights: Improvements in self-control during residential confinement were commonly observed among serious juvenile offenders. These changes are thought to follow from the evidence-based treatments that were received. Self-control improvement predicted improved functioning inside the facility, as well as reduced odds of reoffending for female youth.